Prognostic value of serum S100B concentration in patients with acute spontaneous supratentorial intracerebral hemorrhage - О. A. Koziolkin; A. A. Kuznietsov (Zaporozhye State Medical University, 2021)
Aim of the work - to evaluate the informativeness of serum protein S100B levels in detection of short-term prognosis in patients with acute period of spontaneous supratentorial intracerebral hemorrhage (SSICH) on the background of concervative therapy. Materials and methods. Prospective cohort study of 90 patients with acute SSICH on the background of conservative therapy was done. Level of neurological deficit was evaluated using Full Outline of Unresponsiveness Scale, Glasgow Coma Scale and National Institute of Health Stroke Scale. Computed tomography was done to detect the intracerebral hemorrhage volume (ICHV), secondary intraventricular hemorrhage volume (SIVHV) and total volume of intracranial hemorrhage (TVICH). Laboratory blood samples were taken within 24 hours of hospitalization. Levels of S100B protein in serum were measured using immunoassay analysis. Unfavorable variants of course (early neurological deterioration (END) during 48 hours from hospitalization) and disease acute period outcome of ICH (modified Rankin score 4-6 on the 21st day of the disease) were considered as endpoints. Statistical processing of the obtained results included correlation analysis, logistic regression analysis and ROC-analysis. Results. Neurological deterioration during 48 hours after hospitalization was detected in 18 (20.0 %) patients, unfavorable SSICH acute period outcome was revealed in 49 (54.4 %) patients. It was detected that serum S100B protein correlates with ICHV (R = 0.34, P ˂ 0.01), SIVHV (R = 0.39, P ˂ 0.01) and TVICH (R = 0.45, P ˂ 0.01). Thus, the patients with unfavorable SSICH acute period course and outcome are characterized with the higher S100B protein levels (P ˂ 0.0001). High sensitive multipredicive logistic regression model that integrates prognostic value of serum of S100B protein concentration with informativeness of clinical, neurological parameters (National Institute of Health Stroke Scale score, SIVHV) was elaborated. It helps to detect the individual risk of unfavorable acute SSICH period outcome on the ground of conservative therapy with the accuracy 90.0 % (AUC ± SE (95 % CІ) = 0.95 ± 0.02 (0.89-0.99), P ˂ 0.0001). Conclusions. Serum S100B protein levels in patients with SSICH on the 1st day after hospitalization is the informative additional parameter in verification of short-term prognosis on the background of conservative therapy.